ANAEROBIC ENERGY SUPPLY PROCESSES IN YOUNG MALES OF DIFFERENT SOMATOTYPES FROM THE LOWLAND REGIONS OF ZAKARPATTIA - ДУЛО, Олена; БОЙКО, Надія (ВПЦ "Київський університет" - Publishing center "Kyiv University", 2025)
Background. Human physical health is considered as the degree of development of aerobic and anaerobic energy supply systems for muscle activity. Several scientific studies indicate differences in indicators characterizing anaerobic alactic and anaerobic lactic energy supply modes in individuals of different morphological types. Another factor that must be considered when studying human functional capabilities is the regional factor, as functional abilities are influenced by the level of well-being, regional traditions, dietary habits typical for a particular area, and landscape features. The aim of the study is to determine the characteristics of the development of anaerobic energy supply processes in young men of different somatotypes living in the lowland regions of Zakarpattia. Methods. The study involved 112 young men aged 17–21 years residing in the lowland regions of Zakarpattia. The power of the anaerobic alactic energy system was assessed using the 10-second WAnT 10 test. The power of the anaerobic lactic energy system was assessed using the 30-second WAnT 30 test. The capacity of the anaerobic lactic energy system was determined using the 60-second Shogy & Cherebetin test. Somatotype was determined using the Heath-Carter method. Results. In absolute and relative values of WAnT 10 and WAnT 30, the highest indicators were found in representatives of the mesomorphic and mesoectomorphic somatotypes. The lowest absolute values of WAnT 10 and WAnT 30 were observed in representatives of the ectomorphic and balanced somatotypes. The relative WAnT 10 values of the endomesomorphic somatotype were significantly lower than those of all other somatotypes, while the relative WAnT 30 values of the endomesomorphic somatotype were significantly lower than those of the mesomorphic, mesoectomorphic, and balanced somatotypes. In terms of absolute maximal capacity of the lactic anaerobic energy system, significantly higher values were found in the mesoectomorphic somatotype compared to all other somatotypes, while the lowest values were recorded in the endomesomorphic somatotype compared to the mesomorphic, mesoectomorphic, and balanced somatotypes. Regarding the relative PPO indicator, significantly higher values were observed in the mesoectomorphic somatotype compared to the ectomorphic and endomesomorphic somatotypes. Significantly lower relative PPO values were found in the endomesomorphic somatotype compared to all other somatotypes. Conclusions. Young males of different somatotypes residents in the lowland regions of Zakarpattia significantly differ in the degree of development of anaerobic energy supply processes for muscle activity. The highest values of anaerobic alactic and lactic energy system power were observed in representatives of the mesomorphic and mesoectomorphic somatotypes, where mesomorphy predominates. The highest capacity values of anaerobic lactic energy processes were characteristic of the mesoectomorphic somatotype. The lowest values across all anaerobic performance indicators were observed in the endomesomorphic somatotype, where endomorphy is predominant.

Вступ. Фізичне здоров’я людини прийнято розглядати як ступінь розвитку аеробної та анаеробної систем енергозабезпечення м’язової діяльності. Ряд наукових досліджень вказують на наявність відмінностей за показниками які характеризують анаеробний алактатний та анаеробний лактатний режими енергозабезпечення м’язової діяльності у осіб різних морфологічних типів. Ще одним чинником, який необхідно враховувати при дослідженні функціональних можливостей людини, є регіональний, оскільки на функціональні можливості людини впливають рівень добробуту громадян, традиції їх регіону проживання, особливості харчування характерні для певної місцевості, особливості ландшафту. Мета дослідження – встановити особливості розвитку анаеробних процесів енергозабезпечення м’язової діяльності у юнаків різних соматотипів які мешкають у низинних районах Закарпаття. Методи. У дослідженні взяли участь 112 юнаків віком 17-21 рік, які мешкають у низинних районах Закарпаття. Потужність анаеробної алактатної системи енергозабезпечення визначали за 10-секундним тестом WAnT 10. Потужність анаеробної лактатної системи енергозабезпечення визначали за 30-секундним тестом WAnT 30. Ємність анаеробної лактатної системи енергозабезпечення визначали за 60-секундним тестом Shogy  &  Cherebetin. Соматотип визначали за методом Хіт-Картера. Результати. За абсолютними та відносними показниками ВАнТ 10 і ВАнТ 30 найвищі значення мають представники мезоморфного та мезоектоморфного соматотипів. За абсолютними показниками ВАнТ 10 і ВАнТ 30 нижчі значення виявлено у представників ектоморфного і збалансованого соматотипів. За відносним показником ВАнТ 10 значення представників ендомезоморфного соматотипу вірогідно нижче за значення представників усіх інших соматотипів, а за відносним показником ВАнТ 30 значення представників ендомезоморфного соматотипу вірогідно нижче за значення представників мезоморфного, мезоектоморфного та збалансованого соматотипів. За абсолютним показником МКЗМР вірогідно вищі значення встановлено у представників мезоектоморфного соматотипу по відношенню до представників усіх інших соматотипів, а найнижчі значення у представників ендомезоморфного соматотипу по відношенню до представників мезоморфного, мезоектоморфного та збалансованого соматотипів. За відносним показником МКЗМР вірогідно вищі значення встановлено у представників мезоектоморфного соматотипу по відношенню до представників ектоморфного та ендомезоморфного соматотипів. Вірогідно нижчі значення відносного показника МКЗМР виявлено у представників ендомезоморфного соматотипу по відношенню до представників усіх інших соматотипів. Висновки. Юнаки різних соматотипів які проживають у низинних районах Закарпаття істотно відрізняються за ступенем розвитку анаеробних процесів енергозабезпечення м’язової діяльності. Найвищі значення потужності анаеробних алактатних і лактатних процесів енергозабезпечення характерні для представників мезоморфного та мезоектоморфного соматотипів, у яких домінує мезоморфія. Найвищі значення ємності анаеробних лактатних процесів енергозабезпечення характерні для представників мезоектоморфного соматотипу. Найнижчі значення за усіма показниками анаеробної продуктивності характерні для представників ендомезоморфного соматотипу, у яких домінує ендоморфія.
АНАЕРОБНІ ПРОЦЕСИ ЕНЕРГОЗАБЕЗПЕЧЕННЯ ЮНАКІВ РІЗНИХ СОМАТОТИПІВ НИЗИННИХ РАЙОНІВ ЗАКАРПАТТЯ
Keywords: anaerobic power; anaerobic capacity; somatotype; anaerobic power; anaerobic capacity; somatotype; анаеробна потужність; анаеробна ємність; соматотип; анаеробна потужність; анаеробна ємність; соматотип